A Study on Impact of Human Resource Factors on Knowledge Acquisition and Creation of Sme’s in Health Care Sector - Priya, R.; J. John Adaikalam, Dr. (International Journal of Engineering and Technology, 2018)
Knowledge management has emerged as a new discipline in managing organization. The main objective of this research is to study how far the HR factors like recruitment and selection, training and development, performance appraisal and compensation and rewards influence the knowledge creation and acquisition of SMEâ€™s in healthcare industry. Although, knowledge management has been widely discussed by many academics and practioners, there is relatively little information on knowledge management as found in many fields especially in health care sector.Â The paper aimed at examining the significant of knowledge management, HR factors and to discuss the manner in which HR factors contribute to knowledge creation and acquisition.Â This study will give the solution to the following questions a) what the roles of HRM in knowledge are creation and acquisition b) How far HR practices affect the effectiveness of Knowledge creation and acquisition. Â In this study questionnaire were issued out conveniently to nurses in private hospitals in and around Tambaram, Chennai.Â Out of 106 copies of questionnaire administered, 76 were collected and analyzed. SPSS software was used to analyze, and weighted average and ANOVA are used to prove and disapprove the hypothesis.Â Â Â